Computers: are nurses ready to adapt the new technology - Papagiannaki, Vasileia; Ouzounidou, A; Merkouris, Anastasios (My University, 2001)
Aim: To assess the attitude of nurses towards computers and explore possible correlations with specific background factors. Material-Method: For collecting data, a questionnaire was developed for the specific purposes of the study, based on two dimensions: familiarity — confidence and usefulness of computers. The sample consisted of 650 nurses (364 returned, response rate = 56%) of one big general public hospital. Results: Only 87 subjects (23,9%) had participated in seminars of computers beyond the basic education. The nursing staff showed a moderate to positive attitude (Mean = 3.77. R = 1-5) by recognizing the usefulness of computers (Mean = 3.97) but showing lower confidence and familiarity with them (Mean = 3.36). Regarding the use of computers, almost the 2/3 of the subjects had never used computers. Those who had participated in seminars (Mean = 3.99-3.49, Ρ < 0.001), had computer at home (Mean = 3.91-3.51, Ρ < 0.001) and had used specific computer programs were more positive. The experience and the total attitude of the staff towards computers found to have a weak positive correlation (R = 0.12, Ρ < 0.05). Conclusions: The results can be used in planning and organizing successful computer seminars according to staff needs.